Semantic roles arguments verb in the kurdish language accordind to the model of van valin (2005 ad): (The local bahdin dialect) - Mohammed, Nasreen; Ali, Shirzad (Humanities Journal of University of Zakho, 2023)
The semantics roles are considered one of the important linguistic topics. This research aims at shedding light on the semantic roles that Van Valin (2005 AD) has included, since his model is distinguished from other models of semantic roles, whether in terms of the number of semantic roles or in terms of naming each semantic role. This study has applied this model to the local dialect of Bahdin Kurdish, as it has showed verb arguments according to Van Valin model, because this semantic role is assigned to the argument. The most important questions that have been raised by this study: How many semantic roles are there according to (Van) Valin‌s model (2005 AD) In what case is the word an argument and in what case is it complementary? At the end, the relevant findings have been discussed in terms of Van Valin‌s (2005 AD) models. Moreover, the semantic roles have been divided into three levels, each level contains as aspect of the semantic roles, and it has been able to display 40 thematic relationships. The current study has succeeded to distinguish between arguments and compliments.